Rule-Based Fuzzy Controller for Solid State Transfer Switch Towards Fast Sensitive Loads Transfer - Arsad A.Z.; Hannan M.A.; Lipu M.S.H.; Rahman M.S.A.; Ker P.J.; Mansor M.; Muttaqi K.M.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer circuits; Controllers; Energy transfer; Fault detection; Feeding; Fuzzy control; Fuzzy inference; Fuzzy rules; Power quality; Fault analysis; Faults detection; Feeder; Fuzzy controllers; Fuzzy logic controllers; Fuzzy-Logic; Resistance; Rule based; SSTS system; Quality control